2016
DOI: 10.5194/esurf-4-567-2016
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties of tunnel valleys of the southern sector of the Laurentide Ice Sheet and implications for their formation

Abstract: Abstract. Tunnel valleys have been widely reported on the bed of former ice sheets and are considered an important expression of subglacial meltwater drainage. Although known to have been cut by erosive meltwater flow, the water source and development of channels has been widely debated; ranging between outburst flood events through to gradually occurring channel propagation. We have mapped and analysed the spatial pattern and morphometry of tunnel valleys and associated glacial landforms along the southern se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 98 publications
(239 reference statements)
3
46
1
Order By: Relevance
“…The systems identified by Dyke (1999) as subglacial meltwater channels on Devon Island are approx. 10-20 m wide and 3-6 m deep, which is consistent with subglacial channels observed elsewhere, and 1 to 2 orders of magnitude smaller than tunnel valleys (e.g., Cofaigh, 1996;Kehew et al, 2012;Livingstone and Clark, 2016). Although subglacial channels have been described in detail in the field in northern Europe (e.g., Kleman, 1992;Clark et al, 2004;Piotrowski et al, 2006), the Antarctica Dry Valleys (e.g., Denton et al, 1984;Sugden et al, 1991), Canada (e.g., Kor et al, 1991;Beaney and Shaw, 2000;Shaw, 2002), and the United States (e.g., Walder and Hallet, 1979;Booth and Hallet, 1993), the number of studies addressing their identification from other systems from remote sensing data is limited (Greenwood et al, 2007).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The systems identified by Dyke (1999) as subglacial meltwater channels on Devon Island are approx. 10-20 m wide and 3-6 m deep, which is consistent with subglacial channels observed elsewhere, and 1 to 2 orders of magnitude smaller than tunnel valleys (e.g., Cofaigh, 1996;Kehew et al, 2012;Livingstone and Clark, 2016). Although subglacial channels have been described in detail in the field in northern Europe (e.g., Kleman, 1992;Clark et al, 2004;Piotrowski et al, 2006), the Antarctica Dry Valleys (e.g., Denton et al, 1984;Sugden et al, 1991), Canada (e.g., Kor et al, 1991;Beaney and Shaw, 2000;Shaw, 2002), and the United States (e.g., Walder and Hallet, 1979;Booth and Hallet, 1993), the number of studies addressing their identification from other systems from remote sensing data is limited (Greenwood et al, 2007).…”
supporting
confidence: 88%
“…At lower resolution, in addition, differences among channel direction and local topographic gradients can also be indicative of subglacial erosion, as long as ice erosion rate by sliding is lower than meltwater erosion rate (e.g., Weertman, 1972;Shreve, 1972;Paterson, 1994). Observations of channels incised oblique to topographic gradients are common in the literature (e.g., Sissons, 1961;Walder and Hallet, 1979;Sugden et al, 1991;Livingstone et al, 2017). Quantifying and measuring these deviations in a set of subglacial channels to establish a quantitative base for channel categorization has, however, not been done.…”
Section: Potholesmentioning
confidence: 99%
“…It has been suggested that buried valleys are rare outside areas underlain by poorly consolidated Mesozoic and Cenozoic sediments (Huuse & Lykke-Andersen 2000). However, detailed analyses undertaken as part of this study and others (Lee et al 2015;Livingstone & Clark 2016) have shown this not to be the case. Phillips et al (2010) identify the link between bedrock lithology and the velocity and/or location of faster flowing zones in the overriding ice streams.…”
Section: Effect Of the Substratecontrasting
confidence: 52%
“…Kehew et al (2012) recognize four criteria for identifying tunnel valleys: (i) that they are parallel to ice flow; (ii) they have an undulating convex upward long profile; (iii) they terminate close to or near former ice margins and they are associated with eskers and/or other types of subglacial landforms. This is an idealized list and studies such as those of van der Vegt et al (2012) and Livingstone & Clark (2016) rely more on the morphology of the valleys themselves. Livingstone & Clark (2016) suggest that tunnel valleys often startandendabruptlyandtheup-glacierendoftunnelvalley tends to be rounded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation